PENGOLAHAN LIMBAH CAIR PENCUCIAN KENDARAAN DENGAN SISTEM FILTRASI MENGGUNAKAN FILTER MULTIMEDIA - Meri Selfia; Nur Aida; Arief Rahman (Program Studi Teknik Lingkungan Fakultas Sains dan Teknologi UIN Ar-Raniry Banda Aceh, 2022)
The increase in vehicle washing services has a major impact on the environment, human health and ecosystems in water bodies. One method of treating vehicle washing liquid waste using a filtration system has been proven to be effective and capable of breaking down pollutants contained in wastewater. However, filtration using activated carbon, silica sand, zeolite and gravel media with different variations and doses of media thickness to reduce levels in the parameters pH, TSS, COD and Phosphate has not been studied. This study was conducted to determine the effect of variations and doses of filter media and their effectiveness in reducing the levels of TSS, COD, pH and Phosphate in vehicle washing waste, with variations in the thickness of activated carbon media 10, 20, 25 cm and silica sand, zeolite, gravel 15 , 20 cm. The results showed that activated carbon, silica sand, zeolite and gravel media were able to reduce TSS, COD, pH and phosphate levels. The decrease in levels is highest in the 6th variation. The percentage of TSS is 97.13%, COD is 93.93%, Phosphate is 74% and a decrease in pH 7. From the data presented, it can be seen that all variations are able to reduce levels of pollutant parameters. in vehicle washing waste.